Surviving Heatwaves: Thermal Experience Predicts Life and Death in a Southern Ocean Diatom - Samuels, Toby; Rynearson, Tatiana A.; Collins, Sinéad (Frontiers in Marine Science, 2021)
Extreme environmental fluctuations such as marine heatwaves (MHWs) can have devastating effects on ecosystem health and functioning through rapid population declines and destabilisation of trophic interactions. However, recent studies have highlighted that population tolerance to MHWs is variable, with some populations even benefitting from MHWs. A number of factors can explain variation in responses between populations including their genetic variation, previous thermal experience and the cumulative heatwave intensity (oC d) of the heatwave itself. We disentangle the contributions of these factors on population mortality and post-heatwave growth rates by experimentally simulating heatwaves (7.5 or 9.2 oC, for up to nine days) for three genotypes of the Southern Ocean diatom Actinocyclus actinochilus. The effects of simulated heatwaves on mortality and population growth rates varied with genotype, thermal experience and the cumulative intensity of the heatwave itself. Firstly, hotter and longer heatwaves increased mortality and decreased post-heatwave growth rates relative to milder, shorter heatwaves. Secondly, growth above the thermal optimum before heatwaves exacerbated heatwave-associated negative effects, leading to increased mortality during heatwaves and slower growth after heatwaves. Thirdly, hotter and longer heatwaves resulted in more pronounced changes to thermal optima (Topt) immediately following heatwaves. Finally, there is substantial intraspecific variation in post-heatwave growth rates. Our findings shed light on the potential of Southern Ocean diatoms to tolerate MHWs, which will increase both in frequency and in intensity under future climate change.